Efficacy of Ilizarov Technique in the Treatment of Infected Nonunion of the Tibia - Faraz, Ahmad; Saleem, Muhammad Hassan; Munir, Asad (Biological and Clinical Sciences Research Journal, 2025)
Infected non-union of the tibia remains a significant clinical challenge due to the bone’s subcutaneous location and high risk of complications such as delayed healing and infection. The Ilizarov external fixator is increasingly recognized as an effective method for managing such cases, offering biomechanical stability and facilitating bone regeneration. Objective: To evaluate the outcomes of Ilizarov external fixation in treating infected tibial non-unions, focusing on bone healing, functional results, and complications. Methods: A retrospective study was conducted at the Department of Orthopaedic Surgery, Shaikh Zayed Hospital, Lahore, from January 2022 to December 2023. A total of 52 patients with infected tibial non-union were included. Patient records were reviewed for microbiological findings, duration of treatment, union rates, bone and functional outcomes using the ASAMI (Association for the Study and Application of the Method of Ilizarov) grading system, and complication rates. Results: Staphylococcus aureus was the most commonly isolated organism. At final follow-up, union was achieved in 50 out of 52 patients (96.2%). One patient required amputation due to persistent non-union and sepsis. Based on ASAMI bone results, 23 patients (44.2%) had excellent outcomes, 20 (38.5%) had good outcomes, 6 (11.5%) had fair outcomes, and 3 (5.8%) had poor outcomes. Functional outcomes were satisfactory in the majority of patients. Conclusion: The Ilizarov technique is highly effective for managing infected tibial non-unions. It enables bone union, deformity correction, infection control, and early weight-bearing. Its use should be strongly considered in treating complex tibial non-unions secondary to infection.